Preconcentration and Separation of Gold Nanoparticles from Environmental Waters Using Extraction Techniques Followed by Spectrometric Quantification - Hagarová, Ingrid; Nemček, Lucia; Šebesta, Martin; Zvěřina, Ondřej; Kasak, Peter; Urík, Martin (International journal of molecular sciences, 2022)
The quantification of gold nanoparticles (AuNP) in environmental samples at ultratrace concentrations can be accurately performed by sophisticated and pricey analytical methods. This paper aims to challenge the analytical potential and advantages of cheaper and equally reliable alternatives that couple the well-established extraction procedures with common spectrometric methods. We discuss several combinations of techniques that are suitable for separation/preconcentration and quantification of AuNP in complex and challenging aqueous matrices, such as tap, river, lake, brook, mineral, and sea waters, as well as wastewaters. Cloud point extraction (CPE) has been successfully combined with electrothermal atomic absorption spectrometry (ETAAS), inductively coupled plasma mass spectrometry (ICP-MS), chemiluminescence (CL), and total reflection X-ray fluorescence spectrometry (TXRF). The major advantage of this approach is the ability to quantify AuNP of different sizes and coatings in a sample with a volume in the order of milliliters. Small volumes of sample (5 mL), dispersive solvent (50 µL), and extraction agent (70 µL) were reported also for surfactant-assisted dispersive liquid-liquid microextraction (SA-DLLME) coupled with electrothermal vaporization inductively coupled plasma mass spectrometry (ETV-ICP-MS). The limits of detection (LOD) achieved using different combinations of methods as well as enrichment factors (EF) varied greatly, being 0.004-200 ng L-1 and 8-250, respectively.
Keywords: rozpouštědla; spectrometric methods; gold nanoparticles; separation; kovové nanočástice; quantification; odpadní voda; Waste Water; Wastewater; Gold; Metal Nanoparticles; environmental waters; zlato; povrchově aktivní látky; Surface-Active Agents; Solvents; extraction techniques